Desenvolvimento econômico e qualidade de vida no Brasil : uma análise comparativa entre os municípios costeiros e os municípios não costeiros - Morel, Blanca Lila Gamarra (2018)
The main objective of the thesis is to analyze the level of quality of life between the coastal and non-coastal municipalities of Brazil associated to the environmental, economic and social dimensions. The specific objectives are: to characterize the socioeconomic structure of coastal and non-coastal municipalities and to identify whether there are differences in the quality of life of the population. For that, the approach of human development and economic geography was used as a theoretical reference in order to define quality of life and well-being, as well as the economic and social characteristics that are related to these concepts. The use of this theoretical framework allowed to reach a better definition of the dimensions of analysis and to proceed to the empirical analysis using the Propensity Score Matching (PSM) method. The aim was to identify differences in the quality of life between the coastal and non-coastal areas of Brazil. The empirical analysis suggests evidence contrary to the common sense that in regions with greater potential for concentration of economic activities there is a higher quality of life. Regarding the economic characteristics, the results found corroborate the theory, showing that, in fact, there is a flagrant economic concentration in the coastal municipalities. However, the analysis of environmental and social characteristics showed that although coastal municipalities are more developed from a purely economic point of view, when considered other aspects of development these municipalities perform worse.